WIRELESS COMMUNICATION: A SURVEY OF MALAYSIA TREND, STANDARD & MARKET STUDIES - Chin, Kui Fern (Universiti Malaysia Sarawak, (UNIMAS), 2000)
The wireless telecomlllUlllcatlO11S industry in Malaysia has eXj)erience(I a tremendous transformation in just over a decade. The regulatory aspects were spun offunder the slini looking JTM. This marked the beginning of liberation, and many IINW players en i, ereu the fray. This thesis reviews Llle wireless teleco111III Lill icatlolir iiilrastructllre and services available in Malaysia. Some pertinent issues affecting the industry are also discussed. ']'his thesis also studies wireless telecollllllllnications Industry markets from a new vision and potential viewpoint. The topic is discussed ill terms of environment, technological, and consumer needs. Also, some new thoughts are proposed and the market trend is mentioned. Integrating; synergistically the issues of traffic types, technologies and competition, this create , ) view of the future of wireless telecommunications that appears to he probable and review the technologies likely to be implemented in the future.